Mitochondrial DNA content in blood and carbon load in airway macrophages. A panel study in elderly subjects - Bai, Yang; Casas, Lidia; Scheers, Hans; Janssen, Bram G.; Nemery, Benoit; Nawrot, Tim S. (Environment international, 2018)
Mitochondria are sensitive to air pollutants due to their lack of repair capacity. Changes in mitochondrial DNA copy number (mtDNAcn) or content is a proxy of mitochondrial damage and has been associated with recent exposure to traffic-derived air pollutants, nitrogen dioxide (NO2) and black carbon (BC). Inhaled BC can be phagocytosed by airway macrophages (AMs), and its amount in AM reflects personal exposure to traffic-related air pollution. The present study investigated the relation between the internal marker AM BC and ambient NO2 concentration and examined the associations of mtDNAcn with NO2 and AM BC. A panel of 20 healthy retired participants (10 couples) living in Belgium underwent repeated assessments of health and air pollution exposure at 11 time points over one year. We increased exposure contrast temporarily by moving participants for 10 days to Milan, Italy (high exposure) and to Vindeln, Sweden (low exposure). Personal exposure to NO2 was measured during 5 consecutive days prior to each assessment time point. The amount of BC was assessed by image analysis in AMs retrieved from induced sputum collected at 7 time points. Blood mtDNAcn was determined by qPCR at each time point. Associations between AM BC and NO2, and of mtDNAcn with NO2 and AM BC were estimated using linear mixed effect models adjusted for covariates and potential confounders. Mean concentrations of 5-day average NO2 were higher in Milan (64 μg/m3) and lower in Vindeln (4 μg/m3) than Belgium (26 μg/m3). Each 10 μg/m3 increment in NO2 exposure during the last 5 days was associated with 0.07 μm2 (95% CI: 0.001 to 0.012) increase in median area of AM BC. A 10 μg/m3 increase in NO2 was associated with 3.9% (95% CI: 2.2 to 5.5%) decrease in mtDNAcn. Consistently, each 1 μm2 increment in median area of AM BC was associated with 24.8% (95% CI: 6.8 to 39.3%) decrease in mtDNAcn. In this quasi-experimental setting involving moving persons to places with high and low ambient air pollution, we found changes in AM BC according to ambient air pollution levels measured during the previous 5 days. Both higher ambient NO2 and the internal lung BC load, paralleled mitochondrial compromises as exemplified by lower mtDNA content. •Personal exposure to air pollution was assessed by external and internal markers.•Repeated measures over 1-year and changing places to contrast exposures•Carbon load in airway macrophages was associated with ambient NO2 over a 5-day period.•Decreased blood mitochondrial DNA content in response to higher airway carbon load